The measurement of FBM kuala lumpur composite index towards Islamic Unit Trust in Malaysia: A case study of Ambank Groups (Aminvestment Service Berhad) / Wan Nor Hazirah Wan Mahmud - Wan Mahmud, Wan Nor Hazirah (2011)
This study is about the measurement of FBM Kuala Lumpur Composite Index towards Islamic unit trust in Malaysia. AmBank has been chosen as the case of this study since it is one of unit trust company in Malaysia. The scope of the study started from 1st January 2008 until 30th December 2010 unit trust market return based on Net asset Value (NAV) and FBM Kuala Lumpur Composite Index market return, using weekly basis. The variables of this study is narrowed and focused on variable pricing product only that are the AmIslamic growth, AmPrecious Metals and AmIttikal toward the market performance. The methods use to measure the objectives of the study are simple linear regression. Based on empirical finding the AmIslamic, AmPrecious and Amittikal are influence by the FBM KLCI independent variable. In conclusion, this study rejects the null hypothesis since it shows that all the unit trust performance does have a significant relationship towards FBM KLCI